An analysis of hospital cleaning staff's attitudes and conduct regarding hand hygiene and cleaning - Pirincci, Edibe; Altun, Bengu (Taylor & Francis Ltd, 2016)
Objective. The aim of this study was to analyze the attitudes and conduct of hospital cleaning staff regarding cleaning and hand hygiene. Methods. In May and June 2014, the cleaning staff of Elazig Training and Research Hospital participated in this descriptive research. Data was collected by a survey prepared by the researchers. The SPSS program was used to analyze the data. Results. Of the participants, 70.3% of them were male and their mean age was 38.69 +/- 6.61. The percentage of those hand washing before starting work was 29.8% for primary school graduates or those with lower education. For those with higher levels of education, the percentage was 68.2% (p < 0.001). The percentage of participants who wash their hands after work was 54.3% for primary school graduates and those with lower levels of education. For those with a higher level of education, the percentage was 84.1% (p < 0.001). The participants' use of personal protective equipment during work was that 97.8% of them used gloves, 39.9% bonnets and 56.5% medical masks. Conclusions. The attitudes and conduct of the cleaning staff are not sufficiently hygienic. These employees need training before and throughout their employment.
Keywords: cleaning staff; hand hygiene; cleaning; hospital